FOCUS ON EARLY DIAGNOSIS OF TYPE 1 DIABETES MELLITUS CHILDREN (SYMPOSIUMS ”IDENTIFY AND DO NOT MISS SYMPOSIA: THE FOCUS IS ON CHILDREN WITH IMMUNE-MEDIATED DISEASES” AND ”A NEW CHAPTER IN THE STUDY OF TYPE 1 DIABETES MELLITUS: EARLY DIAGNOSIS COURSE”) - article Editorial (Педиатрическая фармакология)
.